Self-reported hearing loss and visual impairment in adults from Central Mexico - Enrique O Graue-Hernández; Héctor Gómez-Dantés; Martín Romero-Martínez; Gerardo Bravo; Jesús Arrieta-Camacho; Aida Jiménez-Corona (Instituto Nacional de Salud Pública, 2019)
Objective. To determinate the prevalence of hearing loss (HL) and visual impairment (VI) among adult population from Tlaxcala, Mexico. Materials and methods. A population-based cross-sectional study comprising persons 50 years and older was conducted in 2013. Self-reported HL was measured using the Hearing Impairment Inventory for the Elderly (SHIIE) questionnaire; VI was determined using the Snellen tumbling E chart. Results. 900 women and 611 men (mean age 66.1 years) were included. 481(31.8%) individuals had HL (415 alone and 66 combined with VI). Prevalence of HL alone and together with VI was associated with age (per two years, OR=1.03 and OR=1.18, respectively) and self-reported poor health status (OR=1.90 and OR=3.69, respectively). Conclusion. The high prevalence of these disabilities calls for the implementation of public health interventions that help to reduce its impact in the population.